2015
DOI: 10.1074/jbc.m115.676296
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Digital Mapping of N-Methylpurines in Human Cells Reveals Modulation of Their Induction and Repair by Nearest-neighbor Nucleotides

Abstract: Background: N-Methylpurines are repaired by the base excision repair pathway. Results: Induction and repair of N-methylpurines in human cells is significantly affected by nearest-neighbor nucleotides. Conclusion: Modulation of N-methylpurine repair by nearest-neighbor nucleotides is primarily achieved by affecting the initial step of the base excision repair process. Significance: Excision of N-methylpurines by alkyladenine glycosylase is most dramatically affected by sequence context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…We find that repair of 7meG lesions in cellular chromatin is significantly modulated by the translational and rotational setting of the lesion, with faster repair of lesions at "Out" rotational settings and translational positions distal from the nucleosome dyad, including linker DNA, and slower repair at "In" rotational settings and translational positions near the dyad. While these findings are generally consistent with in vitro studies of BER in "designed" nucleosomes (Hinz and Czaja 2015;Rodriguez et al 2015), the effects of translational and rotational setting on BER efficiency have not been previously demonstrated in vivo (Li and Smerdon 2002a;Li et al 2015). These nucleosome-dependent differences in BER efficiency translate to a striking pattern of BER surrounding yeast genes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We find that repair of 7meG lesions in cellular chromatin is significantly modulated by the translational and rotational setting of the lesion, with faster repair of lesions at "Out" rotational settings and translational positions distal from the nucleosome dyad, including linker DNA, and slower repair at "In" rotational settings and translational positions near the dyad. While these findings are generally consistent with in vitro studies of BER in "designed" nucleosomes (Hinz and Czaja 2015;Rodriguez et al 2015), the effects of translational and rotational setting on BER efficiency have not been previously demonstrated in vivo (Li and Smerdon 2002a;Li et al 2015). These nucleosome-dependent differences in BER efficiency translate to a striking pattern of BER surrounding yeast genes.…”
Section: Discussionsupporting
confidence: 82%
“…However, this technique required very high, nonphysiological levels of uracil incorporation (Wyrick and Roberts 2015) and did not measure subsequent repair of uracil lesions. Alternative methods have been proposed for mapping DNA base damage (Li et al 2015;Riedl et al 2016), but these have yet to be applied on a genome-wide scale. Moreover, little is known about how chromatin or other genomic features influence mutagenesis associated with DNA base damage across the genome, due to a lack of relevant genome-wide mutation data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For alkylated DNA lesions, Li et al 116 reported Lesion-Adjoining Fragment Sequencing (LAF-seq) for mapping N -methylpurines in human cells. Briefly, apurinic/apyrimidinic (AP) sites were generated through depurination of N -methylpurines and cleaved by spontaneous β elimination or β and δ eliminations.…”
Section: Recent Development Of Non-lc-ms-based Analysis Of Dna Adductsmentioning
confidence: 99%
“…Many DNA-reactive agents are characterized by a unique spectrum of DNA damage they produce in exposed cells or tissues that is often directly linked to the mutational spectrum. DNA damage mapping is possible at the nucleotide level within specific genes by PCR-based techniques (Denissenko et al, 1996;Li et al, 2015;Pfeifer et al, 1991Pfeifer et al, , 1992. Today, it is of greater interest to develop methodology that can be used to map DNA damage at single base resolution and genome-wide.…”
Section: Introductionmentioning
confidence: 99%